EFEKTIVITAS DIGITALISASI E-PBB TERHADAP KEPATUHAN WAJIB PAJAK: PERAN MODERASI SOSIALISASI PERPAJAKAN - Marhamah Marhamah; Penta Widyartati; Pancawati Hardiningsih (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2026)
Digital transformation in tax administration has become a government strategy to improve the quality of public services and enhance taxpayer compliance. The Semarang City Government has implemented the Electronic Land and Building Tax (E-PBB) system, which enables taxpayers to access tax bill information, make online payments, and monitor their tax obligations more conveniently. However, the level of Land and Building Tax (PBB) compliance in several areas remains suboptimal, indicating that technological convenience alone is insufficient to improve compliance without adequate taxpayer understanding through tax socialization. This study aims to examine the effect of tax service digitalization through the E-PBB system on Land and Building Tax taxpayer compliance and to investigate the moderating role of tax socialization. The study employed a quantitative approach using a survey method involving Land and Building Tax taxpayers in Bubakan Village, Mijen District, Semarang City. Data were collected through questionnaires and analyzed using Moderated Regression Analysis (MRA). The results indicate that tax service digitalization has a positive and significant effect on taxpayer compliance. Tax socialization significantly strengthens the relationship between tax service digitalization and taxpayer compliance. These findings suggest that the successful implementation of digital tax services depends not only on the adoption of technology but also on the effectiveness of tax socialization programs. The findings are expected to provide valuable input for local governments in developing more effective digital tax service policies to improve taxpayer compliance.